How perceived corporate social responsibility and consumer brand preference are linked in pre-emerging economies: the role of brand credibility and brand attitude - Phillip Dangaiso; Paul Mukucha; Divaries Cosmas Jaravaza; Forbes Makudza (Cogent Business & Management, 2024)
Despite the inclusive beneficiation inherent in Corporate Social Responsibility (CSR), emergent literature suggests that it has become a serendipitous differentiation strategy. However, scarce in pre-emerging economies are integrated and robustly tested models linking the CSR dimensions to consumer brand preference. Based on the sustain-centric model, this research examines the impact of perceived economic, social and environmental CSR on corporate brand credibility, consumer brand attitude and consumer brand preference. A causal research design enrolling a Covariance-Based Structural Equation Modelling (CB-SEM) methodology is employed to examine the proposed structural relationships in IBM SPSS AMOS (used under license). Using convenience sampling, customers in the telecommunications sector in Harare were sampled and 266 valid responses estimated model parameters. Positive and significant effects were observed between the dimensions of CSR (perceived economic, environmental and social CSR), corporate brand credibility and consumer brand attitude, save for environmental CSR and consumer brand attitude. Corporate brand credibility positively and significantly influenced both consumer brand attitude and consumer brand preference whilst the positive impact of consumer brand attitude on consumer brand preference was also evident. Our research also contributes that consumers in developing economies relatively score lower in the environmentalism orientation index as the causal link between environmental CSR and consumer brand attitudes did not confirm a positive and significant impact. This paper enlightens corporate managers on the influence of CSR on brand acceptance in consumer markets. Further, it also demonstrates the relative impacts of the CSR dimensions, providing a proxy for resource allocation on competing CSR projects.
Keywords: I38; M14; M31; 650; corporate social responsibility; brand preference; developing economies